Alteration of Peripheral Blood Lymphocytes (PBLs) profile with HBsAg level in patients with chronic hepatitis B infection - Hadi, Qabas Naemah; Mustafa Mahmoud, Mohammed Imad Al-Deen; Hui, Yee Chee; Jaafar, Khairul Azhar; Momtaz, Yadollah Abolfathi (2014)
Chronic hepatitis B infection is associated with dysfunction of cell- mediated immunity. Little is known about the changes of immune response during chronic hepatitis B infection, particularly in correlation between sequential alterations in peripheral blood immune cells population and hepatitis B surface antigen (HBsAg). AIM: to examine the dynamic changes in the population of peripheral blood lymphocyte (PBL) subsets (T cells subsets, B lymphocytes, and NK cells) in healthy donors and patients with CHBI and their correlation with the level of HBsAg (qHBsAg). METHODS: the immunophenotype profiles of PBL of 50(HCV, HDV and HIV negative) chronic hepatitis B patients and 25 healthy controls were analyzed by Flowcytometry (FCM). In addition the serum HBeAg status was determined by ELISA and the HBsAg level was quantified by Elecsys assay (Roche Diagnostics, Germany). Results: significant reduction in both the percentages of CD4+(p≤0.05), CD8+ T lymphocyte subsets and the CD4+/ CD8+ ratio (p<0.01) was found in chronic hepatitis B patients as compared with the healthy donors. Meanwhile, there were no significant differences between patients and healthy controls with regard to other PBL parameters (total T, B, and NK cells), but a significant correlation was observed between HBsAg level and the percentages of T and NK cells (r=0.366; p<0.01, r=-0.462; p<0.05) respectively. Conclusion: our findings confirmed that CHB patients may have adversely affected cell-mediated immunity which is significantly correlated with a higher HBsAg level that leading to progress of the disease these patients.